Hepatocyte mitochondria-derived danger signals directly activate hepatic stellate cells and drive progression of liver fibrosis - Ping An (Nature Portfolio, 2020)
Progressive fibrosis is a driver of morbidity and mortality in many chronic liver diseases, but the underlying mechanisms are incompletely understood. Here, the authors show that mitochondria-derived damage-associated molecular patterns are released from injured hepatocytes and can trigger fibrogenic activation of hepatic stellate cells.